Myocardial Ischemic Subject's Thymus Fat: A Novel Source of Multipotent Stromal Cells. - Wilfredo Oliva-Olivera; Leticia Coín-Aragüez; Julián Salas; Said Lhamyani; Adriana-Mariel Gentile; Esteban Sarria García; Abdelkrim Hmadcha; Hatem Zayed; Antonio Vega-Rioja; Francisco J Tinahones; Rajaa El Bekay (PLoS ONE)
Objective Adipose Tissue Stromal Cells (ASCs) have important clinical applications in the regenerative medicine, cell replacement and gene therapies. Subcutaneous Adipose Tissue (SAT) is the most common source of these cells. The adult human thymus degenerates into adipose tissue (TAT). However, it has never been studied before as a source of stem cells. Material and methods We performed a comparative characterization of TAT-ASCs and SAT-ASCs from myocardial ischemic subjects (n = 32) according to the age of the subjects. Results TAT-ASCs and SAT-ASCs showed similar features regarding their adherence, morphology and in their capacity to form CFU-F. Moreover, they have the capacity to differentiate into osteocyte and adipocyte lineages; and they present a surface marker profile corresponding with stem cells derived from AT; CD73+CD90+CD105+CD14-CD19-CD45-HLA-DR. Interestingly, and in opposition to SAT-ASCs, TAT-ASCs have CD14+CD34+CD133+CD45- cells. Moreover, TAT-ASCs from elderly subjects showed higher adipogenic and osteogenic capacities compared to middle aged subjects, indicating that, rather than impairing; aging seems to increase adipogenic and osteogenic capacities of TAT-ASCs. Conclusions This study describes the human TAT as a source of mesenchymal stem cells, which may have an enormous potential for regenerative medicine.